Emergent Aortic Endovascular Stent Grafts for Ruptured Aortoiliac Aneurysms - Kolbeck, Kenneth J. (Thieme Medical Publishers, 2009)
A ruptured abdominal aortic aneurysm is an emergency anywhere in the world. Physician expertise and clinical status of the patient drive the treatment modalities in the majority of cases. Independent of treatment choice, the goal of therapy is to stabilize the patient as quickly as possible in a manner that establishes maximum survival and minimum morbidity and provides a long-lasting, durable result. Endovascular aortic repair has become an acceptable alternative to open surgical repair in a subset of patients presenting with ruptured aortoiliac aneurysms. Patient selection, physician preference, institutional experience, and availability of appropriate equipment make up a majority of factors influencing treatment choices. Once the decision has been made to treat the patient via endovascular techniques, then experience, planning, and the ability to improvise solutions “on the fly” become vital components to the success of the procedure. Two separate cases, requiring intraprocedural improvisation, are presented followed by a review of the literature.